A revised model for coping with advanced cancer. Mapping concepts from a longitudinal qualitative study of patients and carers coping with advanced cancer onto Folkman and Greer's theoretical model of appraisal and coping. Issue 1 (18th August 2017) - Roberts, Diane; Calman, Lynn; Large, Paul; Appleton, Lynda; Grande, Gunn; Lloyd‐Williams, Mari; Walshe, Catherine
Abstract: Objective: To explore whether the Folkman and Greer theoretical model of appraisal and coping reflects the processes used by people living with advanced cancer. Methods: Interview data from a longitudinal qualitative study with people with advanced (stage 3 or 4) cancer (n = 26) were mapped onto the concepts of the Folkman and Greer theoretical model. Qualitative interviews conducted in home settings, 4‐12 weeks apart (n = 45) examined coping strategies, why people thought they were effective, and in what circumstances. Interviews were coded and analysed using techniques of constant comparison. Results: Mapping coping strategies clearly onto the problem‐ or emotion‐focused elements of the model proved problematic. Fluctuating symptoms, deterioration over time, and uncertain timescales in advanced cancer produce multiple events simultaneously or in quick succession. This demands not only coping with a single event but also frequent repositioning, often to an earlier point in the coping process. In addition, there is substantial ongoing potential for some degree of distress rather than purely "positive emotion" as the final stage in the process is death with several points of permanent loss of capability in the interim. Conclusions: The Folkman and Greer theoretical model is helpful in deconstructing the discrete "problem‐focused" or "emotion‐focused" coping mechanisms participants describe, but its formulation as a linear process with a single, positive, outcome is insufficiently flexible to capture the evolution of coping for people with advanced cancer.